2017
DOI: 10.1111/irv.12514
|View full text |Cite
|
Sign up to set email alerts
|

Human parainfluenza virus infection in severe acute respiratory infection cases in Beijing, 2014‐2016: A molecular epidemiological study

Abstract: BackgroundSevere acute respiratory infection (SARI) threatens human health and even survival, causing a huge number of hospitalized patients every year. However, as one of the most common respiratory viruses circulated worldwide, the epidemiological and phylogenetic characteristics of human parainfluenza virus (HPIV) in these cases were not well known.ObjectivesTo reveal the epidemiological features of HPIV infection in SARIs in Beijing area from September 2014 to August 2016.MethodsA total of 1229 SARI cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
3
25
1
1
Order By: Relevance
“…The most common cause of SARI in children is viral infections [5][6][7][8][9][10], including influenza viruses A and B (Flu A/B); respiratory syncytial virus (RSV); adenovirus (ADV); parainfluenza virus (PIV) 1-3; picornavirus (PIC), which mainly includes human rhinovirus (RV) and human enterovirus (EV); human coronaviruses (HCoV), which includes OC43, 229E, NL63, and HKU; human bocavirus (HBoV); and human metapneumovirus (HMPV). Although the viral and epidemiological profiles of pediatric patients with SARI vary among countries [4,[7][8][9][10][11][12][13][14][15], few studies have comprehensively compared the viral and epidemiological profiles of pediatric patients with SARI in different geographic areas or climate zones within the same country, such as China.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of SARI in children is viral infections [5][6][7][8][9][10], including influenza viruses A and B (Flu A/B); respiratory syncytial virus (RSV); adenovirus (ADV); parainfluenza virus (PIV) 1-3; picornavirus (PIC), which mainly includes human rhinovirus (RV) and human enterovirus (EV); human coronaviruses (HCoV), which includes OC43, 229E, NL63, and HKU; human bocavirus (HBoV); and human metapneumovirus (HMPV). Although the viral and epidemiological profiles of pediatric patients with SARI vary among countries [4,[7][8][9][10][11][12][13][14][15], few studies have comprehensively compared the viral and epidemiological profiles of pediatric patients with SARI in different geographic areas or climate zones within the same country, such as China.…”
Section: Introductionmentioning
confidence: 99%
“…In China, pneumonia is the main cause of child hospitalization which brings about increased burden for outpatient clinic [2,3]. Respiratory virus infections are increasingly recognized as playing a major role in the burden of severe acute respiratory illness in many countries due to expanded global surveillance and improved molecular diagnostic testing [4][5][6][7]. It is reported that among children with pneumonia, 4-10% are caused by human adenovirus (HAdV).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic history of several respiratory viruses isolated from China in recent years have been well established, including the influenza virus ( Wang et al, 2018 ; Yang et al, 2018 ), the PIV ( Pan et al, 2017 ) and the RSV ( Liu et al, 2014 ; Zou et al, 2016 ). The information about adenoviral evolutionary history in China was limited to outbreak reports and novel strains identification ( Lu et al, 2014 ; Li et al, 2018 ), leaving a gap for circulating stains among adult patients.…”
Section: Introductionmentioning
confidence: 99%